Química mineral e parâmetros de cristalização do Granito tipo A Paleoproterozoico Bannach, Província Carajás, Pará - MESQUITA, Caio José Soares (Universidade Federal do Pará, 2019)
The A-type Paleoproterozoic Bannach granite belongs to the Jamon Suíte and cross-cut the Archean units of the Rio Maria Domain in the Carajás Province of the Amazon Craton. It comprises eight facies with varied mafic content.and texture. The dominant amphibole is Fe-hornblende in the more mafic facies and Fe-edenite or hastingsite in the more felsic ones with Fe/(Fe+Mg) ratios of 0.53 to 0.81. In the facies with higher mafic content, it also occurs cummingtonite or grunerite originated from the destabilization of clinopyroxene, with Fe/(Fe+Mg) ratio around 0.50. The biotite is ferroan with Fe/(Fe+Mg) ratio varying between 0.62 and 0.80 except in the late-emplaced medium-grained leucomonzogranites, where it varies from 0.89 to 0.91 and approaches annite in composition. The plagioclase shows normal zoning with sodic andesine or calcic oligoclase cores varying to sodic oligoclase in the more mafic facies and calcic or sodic oligoclase cores and albite borders in the more felsic varieties. The titanite displays Fe/Al ratios similar to those of plutonic magmatic rocks with quartz. Magnetite and ilmenite are significant accessory minerals in all facies. Trellis, composite, individual and patch textural varieties of ilmenite were identified, whereas magnetite occurs in intergrowths with trellis ilmenite, associated with composite ilmenite and in homogeneous crystals associated with cummingtonite-grunerite. There is no significant contrast in composition in the textural varieties of ilmenite, however the ilmenites found in the more felsic granites are enriched in MnO compared to the less evolved ones. The magnetite is always poor in TiO2 and almost Ti-free in the homogeneous crystals. The near liquidus temperatures obtained from the zircon geothermometer vary between 943°C and 795°C, whereas the near solidus temperatures indicated by the amphibole-plagioclase geothermometer are of 807°C to 732 °C, decreasing in both cases from the more mafic to the more felsic granites. The Al-in geobarometer indicated pressures of 300±100 MPa (~11.1±1,9 km) for the emplacement of the Bannach pluton. The Fe/(Fe+Mg) ratios of amphibole and the occurrence of magmatic magnetite and titanite indicate that most granite facies crystallized at moderately oxidizing conditions, however, the biotite compositions indicate for conditions a little more reductive to those of the Jamon magma and the anorogenic granites of the series magnetite of Laurentia. Based on this, it was inferred that the crystallization of the dominant facies in the Bannach Granite occurred under conditions of oxygen fugacity corresponding to those of NNO to NNO -0.5. The late-emplaced medium-grained leucomonzogranites facies is an exception because it displays extremely high Fe/(Fe+Mg) ratios in biotite and approaches the reduced granites of Carajás Province and the ilmenite series granites of Laurentia and Fennoscandia in this regard. This indicates that it crystallized from a magma derived from a more reduced source compared to that of the dominant facies of the Bannach pluton.